Whether We Like It or Not – About Michael McKinnie’s Theory of Theatre-Market Interactions: Book review: Michael McKinnie, “Theatre in Market Economies”, Cambridge: Cambridge University Press, 2021. - TEODORESCU, Marius-Alexandru (Studia Universitatis Babeș-Bolyai Dramatica, 2022)
We have a natural resistance to associate theatre in particular and art in general with anything to do with money or finances. For this reason, Michael McKinnie’s book, Theatre in Market Economies, is not only hard to pallet, but it seems almost outrageous. The book aims to outline the complex relationships between theatre and finances and how theatre makes use of the best strategies of generating capital, often without even realising it. As practitioners, especially in Romania, we tend to see theatre as a poor art, as constantly trying to fight the financial system, and it is a subjective truth, rather than an objective one. McKinnie argues that theatre is high-performance financial engine that makes use of the best strategies that our capitalist world has to offer. This theory is broadly outlined in the introduction, and is further illustrated by examples in the following chapters.